The potential and global outlook of integrated photonics for quantum technologies - Pelucchi, Emanuele; Fagas, Giorgos; Aharonovich, Igor; Englund, Dirk; Figueroa, Eden; Gong, Qihuang; Hannes, Hübel; Liu, Jin; Lu, Chao-Yang; Matsuda, Nobuyuki; Pan, Jian-Wei; Schreck, Florian; et al. (Nature Reviews Physics)
Keywords: General Physics and Astronomy

Improved non-linear devices for quantum applications - Gil López, Jano; Santandrea, Matteo; Roland, Ganaël; Brecht, Benjamin; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Silberhorn, Christine (New Journal of Physics)

Universal compressive tomography in the time-frequency domain - Gil López, Jano; Teo, Yong Siah; De, Syamsundar; Brecht, Benjamin; Jeong, Hyunseok; Silberhorn, Christine; Sánchez-Soto, Luis L. (Optica)

Quantum optical coherence: From linear to nonlinear interferometers - Luo, Kai Hong; Santandrea, Matteo; Stefszky, Michael; Sperling, Jan; Massaro, Marcello; Ferreri, Alessandro; Sharapova, Polina; Herrmann, Harald; Silberhorn, Christine (Physical Review A)

Probing the topological Anderson transition with quantum walks - Bagrets, Dmitry; Kim, Kun Woo; Barkhofen, Sonja; De, Syamsundar; Sperling, Jan; Silberhorn, Christine; Altland, Alexander; Micklitz, Tobias (Physical Review Research)

Transient subdiffusion via disordered quantum walks - Geraldi, Andrea; De, Syamsundar; Laneve, Alessandro; Barkhofen, Sonja; Sperling, Jan; Mataloni, Paolo; Silberhorn, Christine (Physical Review Research)

Statistical Benchmarking of Scalable Photonic Quantum Systems - Tiedau, J.; Engelkemeier, M.; Brecht, Benjamin; Sperling, Jan; Silberhorn, Christine (Physical Review Letters)

Experimental entanglement characterization of two-rebit states - Prasannan, Nidhin; De, Syamsundar; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (Journal of Physics Communications)

Non-Invasive Visualization of Ferroelectric Domain Structures on the Non-Polar y-Surface of KTiOPO4 via Raman Imaging - Brockmeier, Julian; Mackwitz, Peter Walter Martin; Rüsing, Michael; Eigner, Christof; Padberg, Laura; Santandrea, Matteo; Silberhorn, Christine; Zrenner, Artur; Berth, Gerhard (Crystals)
Potassium titanyl phosphate (KTP) is a nonlinear optical material with applications in high-power frequency conversion or quasi-phase matching in submicron period domain grids. A prerequisite for these applications is a precise control and understanding of the poling mechanisms to enable the fabrication of high-grade domain grids. In contrast to the widely used material lithium niobate, the domain growth in KTP is less studied, because many standard methods, such as selective etching or polarization microscopy, provides less insight or are not applicable on non-polar surfaces, respectively. In this work, we present results of confocal Raman-spectroscopy of the ferroelectric domain structure in KTP. This analytical method allows for the visualization of domain grids of the non-polar KTP y-face and therefore more insight into the domain-growth and -structure in KTP, which can be used for improved domain fabrication.

Extremely low-energy ARPES of quantum well states in cubic-GaN/AlN and GaAs/AlGaAs heterostructures - Hajlaoui, Mahdi; Ponzoni, Stefano; Deppe, Michael; Henksmeier, Tobias; As, Donat Josef; Reuter, Dirk; Zentgraf, Thomas; Springholz, Gunther; Schneider, Claus Michael; Cramm, Stefan; Cinchetti, Mirko (Scientific Reports)
Abstract Quantum well (QW) heterostructures have been extensively used for the realization of a wide range of optical and electronic devices. Exploiting their potential for further improvement and development requires a fundamental understanding of their electronic structure. So far, the most commonly used experimental techniques for this purpose have been all-optical spectroscopy methods that, however, are generally averaging in momentum space. Additional information can be gained by angle-resolved photoelectron spectroscopy (ARPES), which measures the electronic structure with momentum resolution. Here we report on the use of extremely low-energy ARPES (photon energy ~ 7 eV) to increase depth sensitivity and access buried QW states, located at 3 nm and 6 nm below the surface of cubic-GaN/AlN and GaAs/AlGaAs heterostructures, respectively. We find that the QW states in cubic-GaN/AlN can indeed be observed, but not their energy dispersion, because of the high surface roughness. The GaAs/AlGaAs QW states, on the other hand, are buried too deep to be detected by extremely low-energy ARPES. Since the sample surface is much flatter, the ARPES spectra of the GaAs/AlGaAs show distinct features in momentum space, which can be reconducted to the band structure of the topmost surface layer of the QW structure. Our results provide important information about the samples’ properties required to perform extremely low-energy ARPES experiments on electronic states buried in semiconductor heterostructures.

Interferometric method for determining the losses of spatially multi-mode nonlinear waveguides based on second harmonic generation - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (Optics Express)

All-dielectric silicon metalens for two-dimensional particle manipulation in optical tweezers - Chantakit, Teanchai; Schlickriede, Christian; Sain, Basudeb; Meyer, Fabian; Weiss, Thomas; Chattham, Nattaporn; Zentgraf, Thomas (Photonics Research)

A dielectric metasurface optical chip for the generation of cold atoms - Zhu, Lingxiao; Liu, Xuan; Sain, Basudeb; Wang, Mengyao; Schlickriede, Christian; Tang, Yutao; Deng, Junhong; Li, Kingfai; Yang, Jun; Holynski, Michael; Zhang, Shuang; Zentgraf, Thomas; et al. (Science Advances)
Compact and robust cold atom sources are increasingly important for quantum research, especially for transferring cutting-edge quantum science into practical applications. In this study, we report on a novel scheme that uses a metasurface optical chip to replace the conventional bulky optical elements used to produce a cold atomic ensemble with a single incident laser beam, which is split by the metasurface into multiple beams of the desired polarization states. Atom numbers ~10 7 and temperatures (about 35 μK) of relevance to quantum sensing are achieved in a compact and robust fashion. Our work highlights the substantial progress toward fully integrated cold atom quantum devices by exploiting metasurface optical chips, which may have great potential in quantum sensing, quantum computing, and other areas.

A photoredox catalysed Heck reaction via hole transfer from a Ru(II)-bis(terpyridine) complex to graphene oxide - Rosenthal, Marta; Lindner, Jörg K N; Gerstmann, Uwe; Meier, Armin; Schmidt, W Gero; Wilhelm, René (Royal Society of Chemistry)

Plasmonic metasurfaces for controlling harmonic generations - Zentgraf, Thomas; Chen, Shumei; Li, Guixin; Zhang, Shuang (Nanoantennas and Plasmonics: Modelling, design and fabrication)

Examination of the evolution of iron oxide nanoparticles in flame spray pyrolysis by tailored in situ particle sampling techniques - Tischendorf, R.; Simmler, M.; Weinberger, C.; Bieber, M.; Reddemann, M.; Fröde, F.; Lindner, J.; Pitsch, H.; Kneer, R.; Tiemann, M.; Nirschl, H.; Schmid, H.-J. (Journal of Aerosol Science)

Influence of lens aberrations, specimen thickness and tilt on differential phase contrast STEM images - Bürger, Julius; Riedl, Thomas; Lindner, Jörg K.N. (Ultramicroscopy)

Waveguide resonator with an integrated phase modulator for second harmonic generation - Stefszky, Michael; Santandrea, Matteo; vom Bruch, Felix; Krapick, S.; Eigner, Christof; Ricken, R.; Quiring, V.; Herrmann, Harald; Silberhorn, Christine (Optics Express)

Metasurfaces help lasers to mode-lock - Sain, Basudeb; Zentgraf, Thomas (Light: Science & Applications)

Polarization-Encrypted Orbital Angular Momentum Multiplexed Metasurface Holography - Zhou, Hongqiang; Sain, Basudeb; Wang, Yongtian; Schlickriede, Christian; Zhao, Ruizhe; Zhang, Xue; Wei, Qunshuo; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (ACS Nano)

Nonlinear imaging with all-dielectric metasurfaces - Schlickriede, Christian; Kruk, Sergey S.; Wang, Lei; Sain, Basudeb; Kivshar, Yuri; Zentgraf, Thomas (Nano Letters)

Second harmonic imaging of plasmonic Pancharatnam-Berry phase metasurfaces coupled to monolayers of WS2 - Spreyer, Florian; Zhao, Ruizhe; Huang, Lingling; Zentgraf, Thomas (Nanophotonics)
The nonlinear processes of frequency conversion such as second harmonic generation (SHG) usually obey certain selection rules, resulting from the preservation of different kinds of physical quantities, e.g. the angular momentum. For the SHG created by a monolayer of transition-metal dichalcogenides (TMDCs) such as WS 2 , the valley-exciton locked selection rule predicts an SHG signal in the cross-polarization state. By combining plasmonic nanostructures with a monolayer of TMDC, a hybrid metasurface is realized, which affects this nonlinear process because of an additional polarization conversion process. Here, we observe that the plasmonic metasurface modifies the light-matter interaction with the TMDC, resulting in an SHG signal that is co-polarized with respect to the incident field, which is usually forbidden for the monolayers of TMDC. We fabricate such hybrid metasurfaces by placing plasmonic nanorods on top of a monolayer WS 2 and study the valley-exciton locked SHG emission from such system for different parameters, such as wavelength and polarization. Furthermore, we show the potential of the hybrid metasurface for tailoring nonlinear processes by adding additional phase information to the SHG signal using the Pancharatnam-Berry phase effect. This allows direct tailoring of the SHG emission to the far-field.

Nonlinear Wavefront Control by Geometric-Phase Dielectric Metasurfaces: Influence of Mode Field and Rotational Symmetry - Liu, Bingyi; Sain, Basudeb; Reineke, Bernhard; Zhao, Ruizhe; Meier, Cedrik; Huang, Lingling; Jiang, Yongyuan; Zentgraf, Thomas (Advanced Optical Materials)
Nonlinear Pancharatnam–Berry phase metasurfaces facilitate the nontrivial phase modulation for frequency conversion processes by leveraging photon‐spin dependent nonlinear geometric‐phases. However, plasmonic metasurfaces show some severe limitation for nonlinear frequency conversion due to the intrinsic high ohmic loss and low damage threshold of plasmonic nanostructures. Here, the nonlinear geometric‐phases associated with the third‐harmonic generation process occurring in all‐dielectric metasurfaces is studied systematically, which are composed of silicon nanofins with different in‐plane rotational symmetries. It is found that the wave coupling among different field components of the resonant fundamental field gives rise to the appearance of different nonlinear geometric‐phases of the generated third‐harmonic signals. The experimental observations of the nonlinear beam steering and nonlinear holography realized in this work by all‐dielectric geometric‐phase metasurfaces are well explained with the developed theory. This work offers a new physical picture to understand the nonlinear optical process occurring at nanoscale dielectric resonators and will help in the design of nonlinear metasurfaces with tailored phase properties.

All-optical switching of a dye-doped liquid crystal plasmonic metasurface - Atorf, Bernhard; Mühlenbernd, Holger; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Optics Express)

Single-channel electronic readout of a multipixel superconducting nanowire single photon detector - Tiedau, Johannes; Schapeler, Timon; Anant, Vikas; Fedder, Helmut; Silberhorn, Christine; Bartley, Tim (Optics Express)
We present a time-over-threshold readout technique to count the number of activated pixels from an array of superconducting nanowire single photon detectors (SNSPDs). This technique places no additional heatload on the cryostat, and retains the intrinsic count rate of the time-tagger. We demonstrate proof-of-principle operation with respect to a four-pixel device. Furthermore, we show that, given some permissible error threshold, the number of pixels that can be reliably read out scales linearly with the intrinsic signal-to-noise ratio of the individual pixel response.
Keywords: Atomic and Molecular Physics; and Optics

Interferometric method for determining the losses of spatially multi-mode nonlinear waveguides based on second harmonic generation. - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (Optics Express)
The characterisation of loss in optical waveguides is essential in understanding the performance of these devices and their limitations. Whilst interferometric-based methods generally provide the best results for low-loss waveguides, they are almost exclusively used to provide characterization in cases where the waveguide is spatially single-mode. Here, we introduce a Fabry-Pérot-based scheme to estimate the losses of a nonlinear (birefringent or quasi-phase matched) waveguide at a wavelength where it is multi-mode. The method involves measuring the generated second harmonic power as the pump wavelength is scanned over the phase matching region. Furthermore, it is shown that this method allows one to infer the losses of different second harmonic spatial modes by scanning the pump field over the separated phase matching spectra. By fitting the measured phase matching spectra from different titanium indiffused lithium niobate waveguides to the model presented in this paper, it is shown that one can estimate the second harmonic losses of a single spatial-mode, at wavelengths where the waveguides are spatially multi-mode.
Keywords: Atomic and Molecular Physics; and Optics

Roadmap on quantum light spectroscopy - Mukamel, Shaul; Freyberger, Matthias; Schleich, Wolfgang; Bellini, Marco; Zavatta, Alessandro; Leuchs, Gerd; Silberhorn, Christine; Boyd, Robert W; Sánchez-Soto, Luis Lorenzo; Stefanov, André; Barbieri, Marco; Paterova, Anna; et al. (Journal of Physics B: Atomic, Molecular and Optical Physics)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics

Single-photon sources: Approaching the ideal through multiplexing - Meyer-Scott, Evan; Silberhorn, Christine; Migdall, Alan (Review of Scientific Instruments)
Keywords: Instrumentation

Distillation of squeezing using an engineered pulsed parametric down-conversion source - Dirmeier, Thomas; Tiedau, Johannes; Khan, Imran; Ansari, Vahid; Müller, Christian R.; Silberhorn, Christine; Marquardt, Christoph; Leuchs, Gerd (Optics Express)
Hybrid quantum information processing combines the advantages of discrete and continues variable protocols by realizing protocols consisting of photon counting and homodyne measurements. However, the mode structure of pulsed sources and the properties of the detection schemes often require the use of optical filters in order to combine both detection methods in a common experiment. This limits the efficiency and the overall achievable squeezing of the experiment. In our work, we use photon subtraction to implement the distillation of pulsed squeezed states originating from a genuinely spatially and temporally single-mode parametric down-conversion source in non-linear waveguides. Due to the distillation, we witness an improvement of 0.17 dB from an initial squeezing value of −1.648 ± 0.002 dB, while achieving a purity of 0.58, and confirm the non-Gaussianity of the distilled state via the higher-order cumulants. With this, we demonstrate the source’s suitability for scalable hybrid quantum network applications with pulsed quantum light.
Keywords: Atomic and Molecular Physics; and Optics

Spatially single mode photon pair source at 800 nm in periodically poled Rubidium exchanged KTP waveguides - Eigner, Christof; Padberg, Laura; Santandrea, Matteo; Herrmann, Harald; Brecht, Benjamin; Silberhorn, Christine (Optics Express)

Spatial entanglement and state engineering via four-photon Hong–Ou–Mandel interference - Ferreri, A; Ansari, V; Brecht, Benjamin; Silberhorn, Christine; Sharapova, Polina R. (Quantum Science and Technology)
Abstract The phenomenon of entanglement is the basis of quantum information and quantum communication processes. Entangled systems with a large number of photons are of great interest at present because they provide a platform for streaming technologies based on photonics. In this paper we present a device which operates with four-photons and based on the Hong–Ou–Mandel interference. The presented device allows to maximize the degree of spatial entanglement and generate the highly entangled four-dimensional Bell states. Furthermore, the use of the interferometer in different regimes leads to fast interference fringes in the coincidence probability with period of oscillations twice smaller than the pump wavelength. We have a good agreement between theoretical simulations and experimental results.
Keywords: Electrical and Electronic Engineering; Physics and Astronomy (miscellaneous); Materials Science (miscellaneous); Atomic and Molecular Physics; and Optics

Detector-Agnostic Phase-Space Distributions - Sperling, Jan; Phillips, D. S.; Bulmer, J. F. F; Thekkadath, G. S.; Eckstein, A.; Wolterink, T. A. W.; Lugani, J.; Nam, S. W.; Lita, A.; Gerrits, T.; Vogel, W.; Agarwal, G. S.; et al. (Physical Review Letters)

Quantum photonics with active feedback loops - Engelkemeier, M.; Lorz, L.; De, Syamsundar; Brecht, Benjamin; Dhand, I.; Plenio, M. B.; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Local Versus Global Two-Photon Interference in Quantum Networks - Nitsche, Thomas; De, Syamsundar; Barkhofen, Sonja; Meyer-Scott, Evan; Tiedau, Johannes; Sperling, Jan; Gábris, Aurél; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

Free and defect-bound (bi)polarons in LiNbO3: Atomic structure and spectroscopic signatures from ab initio calculations - Schmidt, Falko; Kozub, Agnieszka L.; Biktagirov, Timur; Eigner, Christof; Silberhorn, Christine; Schindlmayr, Arno; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)
Polarons in dielectric crystals play a crucial role for applications in integrated electronics and optoelectronics. In this work, we use density-functional theory and Green's function methods to explore the microscopic structure and spectroscopic signatures of electron polarons in lithium niobate (LiNbO3). Total-energy calculations and the comparison of calculated electron paramagnetic resonance data with available measurements reveal the formation of bound polarons at Nb_Li antisite defects with a quasi-Jahn-Teller distorted, tilted configuration. The defect-formation energies further indicate that (bi)polarons may form not only at Nb_Li antisites but also at structures where the antisite Nb atom moves into a neighboring empty oxygen octahedron. Based on these structure models, and on the calculated charge-transition levels and potential-energy barriers, we propose two mechanisms for the optical and thermal splitting of bipolarons, which provide a natural explanation for the reported two-path recombination of bipolarons. Optical-response calculations based on the Bethe-Salpeter equation, in combination with available experimental data and new measurements of the optical absorption spectrum, further corroborate the geometries proposed here for free and defect-bound (bi)polarons.

A photoredox catalysed Heck reaction via hole transfer from a Ru(ii)-bis(terpyridine) complex to graphene oxide - Rosenthal, Marta; Lindner, Jörg; Gerstmann, Uwe; Meier, Armin; Schmidt, Wolf Gero; Wilhelm, René (RSC Advances)
A hole transfer from an excited Ru unit towards graphene oxide significantly improved the photocatalytic activity of the complexes.
Keywords: General Chemical Engineering; General Chemistry

Understanding gray track formation in KTP: Ti^3+ centers studied from first principles - Bocchini, Adriana; Eigner, Christof; Silberhorn, Christine; Schmidt, Wolf Gero; Gerstmann, Uwe (Phys. Rev. Materials)

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Zinc oxide (ZnO) hollow spheres with defined morphology and micro-/nanostructure are prepared by a hydrothermal synthesis approach. The materials possess fine-leaved structures at their particle surface (nanowall hollow micro spheres). Morphology control is achieved by citric acid used as an additive in variable relative quantities during the synthesis. The structure formation is studied by various time-dependent ex situ methods, such as scanning electron microscopy, x-ray diffraction, and Raman spectroscopy. The fine-leaved surface structure is characterized by high-resolution transmission electron microscopy techniques (HRTEM, STEM), using a high-angle annular dark field detector, as well as by differential phase contrast analysis. In-depth structural characterization of the nanowalls by drop-by-drop ex situ FE-SEM analysis provides insight into possible structure formation mechanisms. Further investigation addresses the thermal stability of the particle morphology and the enhancement of the surface-to-volume ratio by heat treatment (examined by N2 physisorption).

Characterisation of width-dependent diffusion dynamics in rubidium-exchanged KTP waveguides - Padberg, Laura; Santandrea, Matteo; Rüsing, Michael; Brockmeier, Julian; Mackwitz, Peter; Berth, Gerhard; Zrenner, Artur; Eigner, Christof; Silberhorn, Christine (Optics Express)

Improving SPDC single-photon sources via extended heralding and feed-forward control - Massaro, Marcello; Meyer-Scott, Evan; Montaut, Nicola; Herrmann, Harald; Silberhorn, Christine (New Journal of Physics)

Characterisation of fabrication inhomogeneities in Ti:LiNbO3 waveguides - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (New Journal of Physics)

Fabrication limits of waveguides in nonlinear crystals and their impact on quantum optics applications - Santandrea, Matteo; Stefszky, Michael; Ansari, Vahid; Silberhorn, Christine (New Journal of Physics)

Counter-propagating photon pair generation in a nonlinear waveguide - Luo, Kai-Hong; Ansari, Vahid; Massaro, Marcello; Santandrea, Matteo; Eigner, Christof; Ricken, Raimund; Herrmann, Harald; Silberhorn, Christine (Optics Express)

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)

Nonlinear optics in all-dielectric nanoantennas and metasurfaces: a review - Sain, Basudeb; Meier, Cedrik; Zentgraf, Thomas (Advanced Photonics)
Free from phase-matching constraints, plasmonic metasurfaces have contributed significantly to the control of optical nonlinearity and enhancement of nonlinear generation efficiency by engineering subwavelength meta-atoms. However, high dissipative losses and inevitable thermal heating limit their applicability in nonlinear nanophotonics. All-dielectric metasurfaces, supporting both electric and magnetic Mie-type resonances in their nanostructures, have appeared as a promising alternative to nonlinear plasmonics. High-index dielectric nanostructures, allowing additional magnetic resonances, can induce magnetic nonlinear effects, which, along with electric nonlinearities, increase the nonlinear conversion efficiency. In addition, low dissipative losses and high damage thresholds provide an extra degree of freedom for operating at high pump intensities, resulting in a considerable enhancement of the nonlinear processes. We discuss the current state of the art in the intensely developing area of all-dielectric nonlinear nanostructures and metasurfaces, including the role of Mie modes, Fano resonances, and anapole moments for harmonic generation, wave mixing, and ultrafast optical switching. Furthermore, we review the recent progress in the nonlinear phase and wavefront control using all-dielectric metasurfaces. We discuss techniques to realize all-dielectric metasurfaces for multifunctional applications and generation of second-order nonlinear processes from complementary metal–oxide–semiconductor-compatible materials.

Engineering integrated photon pair sources and multiplexed detectors (Conference Presentation) - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Eigner, Christof; Harder, Georg; Sansoni, Linda; Nitsche, Thomas; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; et al. (Advances in Photonics of Quantum Computing, Memory, and Communication XII)

Zinc oxide based dielectric nanoantennas for efficient nonlinear frequency conversion - Golla, C.; Weber, N.; Meier, Cedrik (Journal of Applied Physics)

Strong nonlinear optical response from ZnO by coupled and lattice-matched nanoantennas - Protte, Maximilian; Weber, Nils; Golla, Christian; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Nonreciprocal Asymmetric Polarization Encryption by Layered Plasmonic Metasurfaces - Frese, Daniel; Wei, Qunshuo; Wang, Yongtian; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
As flexible optical devices that can manipulate the phase and amplitude of light, metasurfaces would clearly benefit from directional optical properties. However, single layer metasurface systems consisting of two-dimensional nanoparticle arrays exhibit only a weak spatial asymmetry perpendicular to the surface and therefore have mostly symmetric transmission features. Here, we present a metasurface design principle for nonreciprocal polarization encryption of holographic images. Our approach is based on a two-layer plasmonic metasurface design that introduces a local asymmetry and generates a bidirectional functionality with full phase and amplitude control of the transmitted light. The encoded hologram is designed to appear in a particular linear cross-polarization channel, while it is disappearing in the reverse propagation direction. Hence, layered metasurface systems can feature asymmetric transmission with full phase and amplitude control and therefore expand the design freedom in nanoscale optical devices toward asymmetric information processing and security features for anticounterfeiting applications.